(untitled) (The Journal of Psychology and Sociology, 2012)
The subject of study is the effect of the process of information on information behavior and the role of media in society. Findings of the study show the major challenges of the information society and the main directions of information process. The article also describes the main functions of the media and their influence on the formation of personal information culture.